Touch Me - Boos, H. Gordon; Gimpel, Erica; Greg Louganis; Jamie Harris; Kari Wuhrer; Michael Vartan; Peter Facinelli; Amanda Peet (USA Devin Entertainment, 1997)
Bridgette is an actress teaching aerobics, and she falls in love with idle playboy Adam, who runs his father's gym. One day she finds out that one of her ex-lovers died of AIDS and, thinking that Adam is having an affair with another woman, after some hesitation, goes through with the test. She turns out to be positive...
Bridgette is an actress teaching aerobics, and she falls in love with idle playboy Adam, who runs his father's gym...
H. Gordon Boos
Languages : Turkish, English
Subtitle : Turkish
Keywords: Romance; Drama